Unique cellulose/polydimethylsiloxane blends as an advanced hybrid material for organic solvent nanofiltration and pervaporation membranes - Puspasari, Tiara; Chakrabarty, Tina; Genduso, Giuseppe; Peinemann, Klaus-Viktor (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
A novel method for the preparation of cellulose–polydimethylsiloxane (PDMS) blend membranes for organic solvent nanofiltration (OSN) and ethanol pervaporation is presented. The elegance of this approach lies in the use of trimethylsilyl cellulose (TMSC), a hydrophobic cellulose derivative, for blend membrane fabrication followed by simple hydrolysis to convert TMSC back to cellulose. The use of TMSC not only allows cellulose processing in common organic solvents, but also enables the creation of highly compatible cellulose–PDMS blend membranes. The appropriate composition of the blend membrane gave the best OSN performance with more than 10 L m −2 h −1 bar −1 acetone permeance and around 750 Da molecular weight cut-off. This blend membrane can be used for OSN with any other solvents regardless of their polarity. The same membrane also showed an excellent pervaporation performance with a separation factor of 14 and a flux of 1.6 kg m −2 h −1 using a 5 wt% ethanol water mixture at room temperature. The blending of PDMS with cellulose resulted in a 100% increase of the separation factor when compared with pure PDMS. This surprising performance is a consequence of the good miscibility of the blending polymers, which can be obtained through this unique pathway. Overall, this study demonstrates a simple, efficient, and scalable method that is the only possible way reported to date to combine the superiority of cellulose and PDMS as a low-cost and stable membrane for solvent separation.